Suppression of Human Coronavirus 229E Infection in Lung Fibroblast Cells via RNA Interference - Montazeri Aliabadi, Hamidreza; Totonchy, Jennifer; Mahdipoor, Parvin; Parang, Keykavous; Uludağ, Hasan (Frontiers in Nanotechnology, 2021)
Despite extensive efforts to repurpose approved drugs, discover new small molecules, and develop vaccines, COVID-19 pandemic is still claiming victims around the world. The current arsenal of antiviral compounds did not perform well in the past viral infections (e.g., SARS), which casts a shadow of doubt for use against the new SARS-CoV-2. Vaccines should offer the ultimate protection; however, there is limited information about the longevity of the generated immunity and the protection against possible mutations. This study uses Human Coronavirus 229E as a model coronavirus to test the hypothesis that effective delivery of virus-specific siRNAs to infected cells will result in lower viral load and reduced cell death. Two different categories of nucleic acid delivery systems, Peptide/Lipid-Associated Nucleic Acids (PLANAs) and lipophilic polymers, were investigated for their toxicity in human lung fibroblast cells and their ability to deliver specific siRNAs targeting Spike and Envelope proteins in order to prevent cell death in infected cells. Selected siRNAs were effectively delivered to human lung fibroblast cells with negligible toxicity. Cell death due to viral infection was significantly reduced with individual and combinatorial silencing of selected viral proteins. The combinatorial silencing of Spike and Envelope proteins restored the cell viability completely and eliminated plaques in the investigated system. Our cell culture data indicate promising results for the RNAi based approach as an alternative antiviral treatment.